“Enhancing the Sustainability Banking In Indian Banking Sector: A Pathway to Responsible Finance” - Sharma , Aishwarya (Trinity Law Review, 2024)
Sustainable banking, also known as ethical banking or green banking, is a concept where banks focus on making money and consider the environmental and social impacts of their financial activities. It involves making responsible and ethical economic decisions that support the planet’s and society’s well-being. Sustainable banks aim to balance profit-making with environmental conservation, social equity, and ethical practices. They often invest in environ mentally friendly projects, support social initiatives, and adopt eco-friendly banking practices to promote a more sustainable and responsible financial system.